Cr:ZnSe Passively Q-Switched Tm/Ho:YAG Laser With Changeable Wavelengths Between Tm Laser and Ho Laser - Haizhou Huang; Huawen Hu; Jing Deng; Jinhui LI; Kaiming Ruan; Fei Shi; Wen Weng; Wenxiong Lin (IEEE Photonics Journal)
We demonstrate a direct diode-pumped passively Q-switched (PQS) Tm/Ho composite laser with a developed compact hybrid cavity, where the lasing wavelengths were changeable from Ho laser to Tm laser via decreasing initial transmittance of the crystalline Cr:ZnSe saturable absorbers (SAs) from 95%, 92%, to 89%. Using a common 808 nm diode laser as the pump source, maximum average output power of 390 mW, maximum pulse energy of 39 uJ, and the shortest pulse with a full width at half maximum of 22 ns were obtained at lasing wavelengths of 2122 nm, 2090 nm, and 2011 nm respectively, where these peak wavelengths remained stable during the PQS processes with different SAs.